(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
he main problem in this research is about the contribution of Syarif Thayeb to the student movement. To describe the main problems in this research, researchers limit the focus of the study into four questions, such as 1) Background of Syarif Thayeb’s life. 2) What is the role of Syarif Thayeb in the student movement during the Old Order. 3) How was Sharif Thayeb’s effort to suppress the student movement during the New Order. 4) How does his policy make an impact on students This research uses a historical method which consists of four steps of research: heuristics, criticism, interpretation, and historiography. The results of the study can be explained that Syarif Thayeb was elected as the Minister of PTIP and Minister of P and K because of his track record in academia as Chancellor of the University of Indonesia. During his leadership in the Sukarno era, Syarif Tahyeb was very close to students and was one of the initiators of the formation of the Indonesian Student Action Unit (KAMI). Syarif Thayeb, who was a military, felt moved to overthrow the PKI which at that time was considered to have killed military leaders and KAMI who was the actor of the demonstration to disband the PKI. At the time of being appointed Minister of P and K of the new order Syarif Thayeb had a tough task to reduce the student movement which was increase due to the Malari action. Syarif Thayeb finally issued policies which contained restrictions on student movements, even though the policies were reaping opposition from students.